2022
DOI: 10.1038/s41598-022-22334-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous instrumental avoidance learning in social contexts

Abstract: Adaptation to our social environment requires learning how to avoid potentially harmful situations, such as encounters with aggressive individuals. Threatening facial expressions can evoke automatic stimulus-driven reactions, but whether their aversive motivational value suffices to drive instrumental active avoidance remains unclear. When asked to freely choose between different action alternatives, participants spontaneously—without instruction or monetary reward—developed a preference for choices that maxim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 86 publications
4
6
0
Order By: Relevance
“…The current study found the acquisition of costly avoidance of learnt fear, replicating studies examining avoidance of learnt fear via higher-order conditioning procedures (Klein et al, 2021;Wong & Pittig, 2022b) and generally the acquisition of avoidance of learnt fear (e.g., Mennella et al, 2022;Pittig et al, 2014;Rinck et al, 2016). This was evident in two patterns.…”
Section: Discussionsupporting
confidence: 77%
“…The current study found the acquisition of costly avoidance of learnt fear, replicating studies examining avoidance of learnt fear via higher-order conditioning procedures (Klein et al, 2021;Wong & Pittig, 2022b) and generally the acquisition of avoidance of learnt fear (e.g., Mennella et al, 2022;Pittig et al, 2014;Rinck et al, 2016). This was evident in two patterns.…”
Section: Discussionsupporting
confidence: 77%
“…These findings, which align with the results for spontaneous approach/avoidance decision to task-irrelevant emotional faces ( Mennella et al. 2020 , 2022 , Vilarem et al. 2020 , Grèzes et al 2021 ), show how emotional information can drive adaptive behavior in the absence of conscious experience, challenging a systematic inference of emotional states from behavior.…”
Section: Are Times Mature To Build Theories Of Emotional Consciousnes...supporting
confidence: 81%
“…2017 , LeDoux and Daw 2018 , Mendl and Paul 2020 ). This is corroborated by the fact that goal-directed approach/avoidance behaviors to emotional stimuli can be elicited in the absence of a reportable strategy for action ( Mennella et al 2022 ) and in the absence of stimulus awareness ( Vetter et al. 2019 ).…”
Section: Experimental Contrasts and What Can(not) Be Inferredmentioning
confidence: 78%
“…While, to our knowledge, studies manipulating action controllability when facing emotional expressions are still lacking, arbitration between stimulus-driven and goal-directed modes was recently tested in a study on spontaneous avoidance learning in social contexts. The results showed that, without instruction, participants learned, in a volatile environment, which action (sitting on the left or right chair) was associated with a higher probability of avoiding an angry individual, with or without their developing awareness of the avoidance strategy (Mennella et al, 2022). Goal-directedness in behavior, as opposed to simple response perseverance, was higher in participants having developed a reportable avoidance strategy and was correlated with how subjectively negative the approaching angry individual was valued.…”
Section: Arbitrating Between Action Control Modes When Facing Emotion...mentioning
confidence: 93%
“…Moreover, humans can spontaneously learn (without instruction) which action leads more often to the avoidance of angry individuals, without developing an explicit avoidance strategy (Mennella et al, 2022).…”
Section: -License CC Bymentioning
confidence: 99%